Online monitoring and sampling analysis of siltation in the middle route of the south-to-north water diversion project - Zhang, Dawei; Han, Xiaolin; Zhong, Qiang; Wang, Shulei; Ding, Liuqian; Liu, Yuan; Chen, Qigang; Wang, Fujun (Frontiers in Environmental Science, 2022)
The middle route project (MRP) of the South to North Water Diversion Project is a significant infrastructure and alleviating water scarcity in Northern China. MRP suffered from untraditional sediment problems. Obvious siltation occurred in the regulating reservoir at the end of the channel and some locations with weak hydrodynamic conditions in the channel when the mineral sediment concentration in the flow is very low. To study the characteristics of the sediment and the siltation time period, an IoT based automatic siltation monitoring system using cloud was installed at the outlet of the inverted siphon project on Xiao River. Three years of online monitoring data since 2018 and the siltation samples at five sites for particle size analysis were collected. The monitoring data shows that siltation mainly occurs during March to October, and almost no siltation occurs in winter. The maximum siltation speed can reach 390mm per day. The particle size of the siltation gradually increases from upstream to downstream, which mainly occurs in the range above 100m. The organic matter contained in the siltation shows a significant increase from 40.3% to 86.4% at upstream and downstream sampling position, respectively. Monitoring results shows the main body of the siltation in the MRP is not the traditional sediment but the remnants of the algae that proliferate in large numbers. During March to October, the temperature is suitable for the proliferation of algae which attaches to the sediment particles and gradually grows downstream with the flow.